(untitled) (Configurazioni. Research on contemporary poetry, 2023)
This paper aims to examine the relationship between poetry and the public. The first part is dedicated to the more traditional ways of circulation of the poetic text, the anthology and the poetry series, which are connected to the most significant publishing experiences of the twentieth century. The second part instead is focused on poetry as performance, developed starting from the poetry slam experiences, which marks a significant change in the methods of diffusion of the poetic genre.